2013
DOI: 10.5194/bg-10-6639-2013
|View full text |Cite
|
Sign up to set email alerts
|

Calcification intensity in planktonic Foraminifera reflects ambient conditions irrespective of environmental stress

Abstract: Planktonic Foraminifera are important marine calcifiers, and the ongoing change in the oceanic carbon system makes it essential to understand the influence of environmental factors on the biomineralization of their shells. The amount of calcite deposited by planktonic Foraminifera during calcification has been hypothesized to reflect a range of environmental factors. However, it has never been assessed whether their calcification only passively responds to the conditions of the ambient seawater or whether it r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 50 publications
1
54
0
1
Order By: Relevance
“…Our results show that for a given species, SNW is not statistically different regarding the hydrography but that SNW varies significantly between the dominant species N. pachyderma, T. quinqueloba and G. bulloides. This suggests that ecological conditions other than the carbon chemistry of ambient seawater at long (Weinkauf et al, 2013) and short time scale (de Villiers, 2004;Marshall et al, 2013), and species physiological characteristics and metabolism might be responsible for the three-fold SNW increase between T. quinqueloba and G. bulloides. This has potentially important implications for the carbon pumps because it implies that planktic foraminifer community composition together with the magnitude of the numerical flux (number of individuals) plays a role in the foraminifer-mediated PIC flux.…”
Section: Foraminifer Test Size and Snw Distributionmentioning
confidence: 98%
“…Our results show that for a given species, SNW is not statistically different regarding the hydrography but that SNW varies significantly between the dominant species N. pachyderma, T. quinqueloba and G. bulloides. This suggests that ecological conditions other than the carbon chemistry of ambient seawater at long (Weinkauf et al, 2013) and short time scale (de Villiers, 2004;Marshall et al, 2013), and species physiological characteristics and metabolism might be responsible for the three-fold SNW increase between T. quinqueloba and G. bulloides. This has potentially important implications for the carbon pumps because it implies that planktic foraminifer community composition together with the magnitude of the numerical flux (number of individuals) plays a role in the foraminifer-mediated PIC flux.…”
Section: Foraminifer Test Size and Snw Distributionmentioning
confidence: 98%
“…For size-normalisation of shell weight measurements, we follow the "area density" (ρ A ) approach of Marshall et al (2013), as used elsewhere (Weinkauf et al, 2013(Weinkauf et al, , 2016Marshall et al, 2015;Osborne et al, 2016). From each core-top sample, individual specimens (n = 8-26) of G. ruber sensu stricto and sensu lato were picked from discrete sieve size fractions, imaged (umbilical side up), and weighed, and their cross-sectional or silhouette area determined using Macnification (Orbicule Inc., v2.0).…”
Section: Core-top Samplingmentioning
confidence: 99%
“…Our modelling approach shows that there is in fact a strong effect of test size on SNW. Modelled area density (ρ A , a commonly used SNW metric Marshall et al, 2013Marshall et al, , 2015Osborne et al, 2016;Weinkauf et al, 2013Weinkauf et al, , 2016) is shown in Fig. 6a as a function of test diameter.…”
Section: Implications For Size-normalised Weight (Snw) In Foraminifermentioning
confidence: 99%
See 2 more Smart Citations